Bone Remineralization around Dental Implants following Conservative Treatment after Peri-Implantitis - Algirdas Puisys; Viktorija Auzbikaviciute; Renata Simkunaite-Rizgeliene; Dainius Razukevicius; Rokas Linkevicius; Tomas Linkevicius (Hindawi Limited, 2019)
The aim of this case report is to show that bone remineralization around dental implants with a history of peri-implantitis is possible after irritant factors are removed and only conservative treatment is performed. Patient came to the clinic after three years of dental implant placement complaining about swelling, sensitivity and gingiva color changes at the posterior part of the maxilla. During radiographic and intraoral examinations peri-implantitis of the #24 implant site was diagnosed. The surgical treatment method was rejected and performed conservative treatment instead. The outcome is promising; periapical radiographs three months later showed bone remineralization as well as stable bone after 10 years. A key clinical message: Bone remineralization around dental implants with a history of peri-implantitis is possible after irritant factors are removed and conservative treatment performed.